2020
DOI: 10.14814/phy2.14340
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose caffeine administration increases fatty acid utilization and mitochondrial turnover in C2C12 skeletal myotubes

Abstract: Caffeine has been shown to directly increase fatty acid oxidation, in part, by promoting mitochondrial biogenesis. Mitochondrial biogenesis is often coupled with mitophagy, the autophagy-lysosomal degradation of mitochondria. Increased mitochondrial biogenesis and mitophagy promote mitochondrial turnover, which can enhance aerobic metabolism. In addition, recent studies have revealed that cellular lipid droplets can be directly utilized in an autophagy-dependent manner, a process known as lipophagy. Although c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…29,30 Caffeine, the main active component of C. arabica, is reported as a potent activator of autophagy that acts by different mechanisms, increasing LC3 autophagosomal marker expression in neuronal, liver, muscle, and heart cells, inhibiting mTOR complex 1 in the liver, muscle, and heart cells, inducing lipophagy in skeletal myotubes and hepatic cells, and protecting skin from oxidative stress and cell senescence induced by ultraviolet radiation via activation of adenosine monophosphateactivated protein kinase (AMPK)-mediated autophagy in human keratinocytes. 7,[32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Caffeine, the main active component of C. arabica, is reported as a potent activator of autophagy that acts by different mechanisms, increasing LC3 autophagosomal marker expression in neuronal, liver, muscle, and heart cells, inhibiting mTOR complex 1 in the liver, muscle, and heart cells, inducing lipophagy in skeletal myotubes and hepatic cells, and protecting skin from oxidative stress and cell senescence induced by ultraviolet radiation via activation of adenosine monophosphateactivated protein kinase (AMPK)-mediated autophagy in human keratinocytes. 7,[32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…We decided to use drugs whose acute effects on force production could be potentially assessed in a short time frame. Caffeine [19][20][21][22][23][24][25][26][27]9] and verapamil [28,29,9] have opposite effects on calcium dynamics in muscle fibers. Caffeine is an agonist of the ryanodine receptor (RyR) on the SR, inducing a greater calcium flux towards the cytosol and therefore ultimately promoting higher contraction forces.…”
Section: The Cuore Allows For Real-time Tracking Of Drug Effectsmentioning
confidence: 99%
“…It has been demonstrated to reduce the autophagy-dependent lipid concentration in hepatic tissues through lipophagy [ 89 ]. Besides, caffeine also demonstrated that to activate mitophagy for increasing fatty acid oxidation as well as mitochondrial biogenesis as accompanied with potentiated the rate of mitochondrial degradation in skeletal muscle [ 77 ].…”
Section: Caffeine With Mitophagy On T2dmmentioning
confidence: 99%